Second Five Year Road Development Plan 3. Transport & Communication 31. Roads Estimated Cost of Schemes Rs 899.00 Lacs. Rajasthan State - Planning Commission (Planning Commission, 1956)
Head of Development Transport and Communications Plan Expenditure 1956=61, Head of Development Transport and Communications Expenditure on Revenue and Capital Account, Head of Development Transport and Communications Target of Work/Capacity (Total Mileage Per Year), Man-Power Required- Construction Phase, Plan Expenditure 1956-61.
Rajasthan State
Rajasthan State